2006
DOI: 10.1021/la0601657
|View full text |Cite
|
Sign up to set email alerts
|

Directing Droplets Using Microstructured Surfaces

Abstract: Systematic variation of microscale structures has been employed to create a rough superhydrophobic surface with a contact angle gradient. Droplets are propelled down these gradients, overcoming contact angle hysteresis using energy supplied by mechanical vibration. The rough hydrophobic surfaces have been designed to maintain air traps beneath the droplet by stabilizing its Fakir state. Dimensions and spacing of the microfabricated pillars in silicon control the solid-liquid contact area and are varied to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
231
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(233 citation statements)
references
References 32 publications
2
231
0
Order By: Relevance
“…In terms of wetting, the roughness and solid surface fraction properties are not one's of the surface itself, but of the surface sampled locally by the contact line of the liquid. This variation in pattern with position can be used to produce a pattern of surface wettability with variation of the local contact angle from one side of a droplet to the other and so create a driving force to direct the motion of a droplet [11,27,28,29]. Whether motion occurs depends on droplet size and the contact angle hysteresis.…”
Section: Important Considerations When Using Wenzel and Cassie-baxtermentioning
confidence: 99%
“…In terms of wetting, the roughness and solid surface fraction properties are not one's of the surface itself, but of the surface sampled locally by the contact line of the liquid. This variation in pattern with position can be used to produce a pattern of surface wettability with variation of the local contact angle from one side of a droplet to the other and so create a driving force to direct the motion of a droplet [11,27,28,29]. Whether motion occurs depends on droplet size and the contact angle hysteresis.…”
Section: Important Considerations When Using Wenzel and Cassie-baxtermentioning
confidence: 99%
“…5), and their mixture with external field. 86) In these surfaces, a Laplacian pressure difference is generated between advancing and receding sides of the liquid: the liquid droplets move spontaneously.…”
Section: Motion Of Water Droplet On Hydrophobic Surface 41 Droplet Mmentioning
confidence: 99%
“…It has been proved that anisotropic wetting can be achieved by spatial gradients (surface chemistry and morphology) or asymmetric asperities. 8,9) For example, Kubiaka et al 10) theoretically studied the influence of hydrophobic and hydrophilic materials on anisotropic wetting by Lattice Boltzmann Method. Zhao et al 11) reported roughness exerted an effect on anisotropic wetting on submicrometer-scale periodic structures consisting of parallel grooves by laser interference.…”
Section: Introductionmentioning
confidence: 99%